Use of Controlled-Release Urea to Improve Yield, Nitrogen Utilization, and Economic Return and Reduce Nitrogen Loss in Wheat-Maize Crop Rotations - Xinpeng Xu; Ping He; Jianlin Wei; Rongzong Cui; Jingxia Sun; Shaojun Qiu; Shicheng Zhao; Wei Zhou (Agronomy, 2021)
Excessive nitrogen (N) fertilizer input has become a common phenomenon among most farmers in the winter wheat–summer maize rotation system of north-central China, and has resulted in low nutrient use efficiency and environmental pollution. Controlled-release urea (CRU) is proposed as a solution to excessive fertilization because CRU achieves high yields and reduces N losses. Therefore, CRU mixed with normal urea at rates based on the Nutrient Expert (NE) system was used as fertilizer in a 4-year field experiment to test the preference in crop yields, economic benefits, nitrogen use efficiencies, and N losses. The following fertilizer treatments were established: local farmers’ practices (FP); normal urea fertilizer at the rate recommended by the NE system (NE); mixed CRU and normal urea at ratios of 60:40 (CRU1) and 75:25 (CRU2) based on the NE system; and 80% of the recommended N rate of the NE, CRU1 and CRU2 treatments (80%NE, 80%CRU1 and 80%CRU2). The results showed that, compared with the NE treatment at the same application rate of N, mixed CRU and urea increased yields and net benefits while reducing N loss. The application of CRU at 60% for maize and 75% for wheat had the best overall effects. Compared with FP, the average grain yield, recovery efficiency of N fertilizer and net benefits increased by 8.5%, 10.9% and 11.3%, respectively, for maize with CRU1, and increased by 4.5%, 15.1% and 10.3%, respectively, for wheat with CRU2. Furthermore, mixed CRU and urea at the recommended N rate significantly reduced N loss from 38.5% to 40.3% but increased soil NO3−-N and NH4+-N contents at 0–30 cm, although opposite results (NO3−-N) were observed deeper in the soil (30–90 cm). In the treatments 80%CRU1 and 80%CRU2, the maize yield and overall economic benefits were equivalent to those in the FP treatment, but apparent N loss was significantly reduced. Thus, these results confirmed that the combination of the CRU and the NE system for winter wheat–summer maize in north-central China is efficient and valuable, and has the potential to improve yield, nitrogen use efficiency and net benefit with low N losses.